COMPETENCIES OF PRIMARY CARE PHYSICIANS IN THE DIAGNOSIS AND PREVENTION OF GYNECOLOGICAL DISEASES - Gulnara Asadova (Modern American Journals, 2025)
Primary care physicians play a key role in ensuring women’s reproductive health through the early diagnosis and prevention of gynecological diseases. As the first point of contact within the healthcare system, they are responsible for identifying initial clinical signs, assessing risk factors, and initiating timely preventive and diagnostic measures. This study focuses on the core competencies required of primary care physicians in the diagnosis and prevention of gynecological diseases, including clinical evaluation skills, implementation of screening programs, preventive counseling, and effective referral to specialized care. Strengthening these competencies contributes to early disease detection, reduction of complications, and improvement of overall women’s health outcomes.
Keywords: Primary care physician; gynecological diseases; early diagnosis; prevention; women’s health; clinical competencies.